Dampak Latihan Self Efficacy Terhadap Kemampuan Self Care Pasien Di Ruang Interna Rsud Syarifah Ambami Rato Ebuh Bangkalan - muhammad Suhron (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Nursing ability to prevent and minimizethemselves due to the risk of a disease is not thesame on every person. One theory that is beingdeveloped in the world of nursing theory DorotheaElisabeth Orem is that the theory of self-care. Basedon preliminary studies obtained largely self-careabilities of patients in interne room is low. Thepurpose of this study to analyze differences in theability of self-care in patients before and after selfefficacy exercise. This type of research is the preexperimental with one-group pre-post test design.The samples used were 15 people with a purposivesampling technique. Data collection was conductedusing a checklist sheet classification of self careability and Wilcoxon test to see the difference. Thestatistical result is obtained p-value (0,001) < α(0,05) which means that H1 is accepted and H0 isrejected or there are difference in the ability of selfcare before and after self-efficacy exercise in theinterne room Syarifah Ambami Rato EbuhBangkalan. This was caused by the self-efficacyexercise can affect cognitive, motivational, affective,and selection. In connection with the development of theoryin nursing, it is expected that health workers to betterunderstand the importance of improving the ability ofself-care to maintain the normal function of the bodyby making self-efficacy exercise as a measure ofnursing care at the Hospital